Youth-Adult Partnership: A New Way Forward for Greater Muslim Youth Participation in Schools and Communities - steven eric krauss (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2015)
Young people in Muslim majority countries are a valuable asset and investing in them can bring tremendous social and economic benefits. They also face many challenges that undermine their ability to develop and contribute to society. To make the most of the opportunity, these countries must find ways to increase the human and social capital of their respective youth populations. Youth participation in formal and non-formal educational settings such as schools and community programs has been identified as an effective approach to enhancing young people’s experiences. Building on initial findings from Malaysia, the current paper puts forth the concept of youth-adult partnership (Y-AP) as a strategy for schools. Y-AP has been shown to enhance personal agency, empowerment and connection to community, three attributes that are critical for Muslim youth to play more substantive roles in national development. The paper further attempts to frame Y-AP within an Islamic socio-historical lens, drawing on examples from the Prophet Muhammad SAW and the early Muslim community to show how developmental relationships were central to the social and educational culture within the Prophet’s community. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2810